1998
DOI: 10.1172/jci119878
|View full text |Cite
|
Sign up to set email alerts
|

GAD-reactive CD4+ Th1 cells induce diabetes in NOD/SCID mice.

Abstract: Although glutamic acid decarboxylase (GAD) has been implicated in IDDM, there is no direct evidence showing GAD-reactive T cells are diabetogenic in vivo. To address this issue, 3-wk-old NOD mice received two injections of purified rat brain GAD; one mouse rapidly developed diabetes 3 wk later. Splenocytes from this mouse showed a proliferative response to purified GAD, and were used to generate a CD4+ T cell line, designated 5A, that expresses TCRs encoding Vbeta2 and Vbeta12. 5A T cells exhibit a MHC restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
117
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 34 publications
0
117
0
2
Order By: Relevance
“…Moreover, the disease can be transferred to NOD/SCID mice by CD4+ T-cell clones in the total absence of CD8+ cells [18,19,20]. These important observations strongly suggest that CD4+ T cells are capable of destroying beta cells in an antigen-specific manner.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the disease can be transferred to NOD/SCID mice by CD4+ T-cell clones in the total absence of CD8+ cells [18,19,20]. These important observations strongly suggest that CD4+ T cells are capable of destroying beta cells in an antigen-specific manner.…”
Section: Discussionmentioning
confidence: 93%
“…One repertoire is primed spontaneously in vivo (against GAD(530 -543) (p530)) and is associated with ␤ cell autoimmunity, the other is regulatory and inducible after immunization with GAD65(524 -543) or GAD(524 -543) (p524). Although GAD-reactive T cells may possess diabetogenic activity (10) and GAD expression appears to be required for ␤ cell damage to occur in the NOD mouse model (8), GAD65 or certain of its peptides also have the ability to prevent the spontaneous development of IDDM in NOD mice when they are administered in a specific manner (i.v., mucosally, or i.p.) (1, 2, 9, 16).…”
Section: Two Distinct Cd4 ϩ T Cell Repertoires Within Gad65(524 -543)mentioning
confidence: 99%
“…However, despite its prominence as a target during disease progression, it is only with rare exception that autoimmune diabetes has been associated with the delivery of GAD65 or GAD65 peptides into NOD mice (9,10). In this report, we address the distinction between the GAD65(524 -543)-specific CD4 ϩ T cells which spontaneously arise in the NOD mouse (1) and those that are activated as a result of immunization with this peptide (11).…”
mentioning
confidence: 99%
“…Interestingly, this 20mer peptide appeared to be comprised of two distinct determinants: an N-terminal moiety (p524-538 (p524)) and a C-terminal moiety (p530-543 (p530)). Importantly, two distinct T cell populations could be induced by these two overlapping peptides, and it appeared that they had opposing functions: the p530-specific T cells are invasive and may be pathogenic [21,22], whereas the p524-specific T cells are regulatory in nature and can prevent diabetes by adoptive transfer [23]. In this study, we mapped the fine specificity of clones specific for either p524 or p530 to define the minimal antigenic cores of these two determinants, and found that p543 contains multiple epitopes containing a central overlapping core sequence, p530-539, with different lengths of flanking residues at their N or C termini.…”
mentioning
confidence: 99%